2017
DOI: 10.1016/j.apergo.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bicycle setup for children based on anthropometrics and comfort

Abstract: Bicycling is a popular activity for children. In order for children to enjoy cycling and to minimize injury, it is important that they are positioned appropriately on the bicycle. The purpose of this study was therefore to identify a suitable bicycle setup for children aged between 7 and 16 years which accommodates developmental differences in anthropometrics, flexibility and perceptions of comfort. Using an adjustable bicycle fitting rig, we found the most comfortable position of 142 children aged 7 to 16. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…If there is a correlation between the anthropometric measures and reach, this would allow for the determination of a regression equation that will help identify the fit window for postural reach. This equation would provide the fitters with a better starting point for determining reach than what currently amounts to an educated guess 11 . If found, this correlation could allow for improved fit, comfort, and possibly help improve the link between fit and non-traumatic stress injuries.…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…If there is a correlation between the anthropometric measures and reach, this would allow for the determination of a regression equation that will help identify the fit window for postural reach. This equation would provide the fitters with a better starting point for determining reach than what currently amounts to an educated guess 11 . If found, this correlation could allow for improved fit, comfort, and possibly help improve the link between fit and non-traumatic stress injuries.…”
Section: Research Problemmentioning
confidence: 99%
“…This is similar to the findings of Grainger, Dodson, and Korff 11 , though they also found a correlation with trunk length, which this study failed to find. It should be noted that the authors were examining children 11 . The only other study that examined anthropometrics of the upper extremity length was conducted by Baino 21 , who did not determine that a correlation existed.…”
Section: Evaluation Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of the cycling trials, HR matched and VO2 matched, was randomized. Each participant was fitted to the bike based on the recommendations of Grainger, Dodson, & Korff (2017).…”
Section: Cyclingmentioning
confidence: 99%
“…Altogether, the review revealed that no investigation has been done to understand the connection between rider's physical and motorcycle design attributes (like comfortable riding position). However, Grainger et al 21 investigated the association between the anthropometry and comfortable posture (joint angles)/position of two-wheelers (bicycle) riders using multiple regression analysis. Though the regression model was moderate (R 2 \ 0.4), they established a significant relationship between comfortable posture joint angle (like torso angle, arm angle, etc.)…”
Section: Introductionmentioning
confidence: 99%